Biological Activity of Cassidula nucleus Extract from Semarang Waters - Salsabilla, Sauwa Khusna; Pringgenies, Delianis; Gaol, Josua Gabriel Lumban (Masyarakat Moluska Indonesia, 2025)
Molluscs are triploblastic coelomate metazoan organisms from the invertebrate phylum that have secondary metabolite profiles. Secondary metabolites of molluscs are formed due to adaptation to the surrounding environment. This study aims to analyse the secondary metabolite profiles of Cassidula nucleus species from Semarang waters. Cassidula nucleus samples were obtained from the mangrove ecosystem in Mangkang, Semarang, used the purposive sampling method. The methods used in this study include maceration extraction to extract compounds from mollusc samples, thin layer chromatography (TLC) tests for the separation and identification of metabolites, and antibacterial tests to evaluate the potential of the resulting mollusc extract. Maceration extraction was carried out using ethanol in a 1:7 ratio for 48 hours. The antibacterial tests was conducted on the pathogenic bacteria Eschericia coli and Staphylococcus aureus using the disc diffusion method. The extract concentrations tested were 1000 μg/disc, 500 μg/disc, 250 μg/disc, 125 μg/disc, and 62.5 μg/disc. Observations were made every 12 hours for a total of 36 hours. The research results indicated that the positive extract contained flavonoid and alkaloid compounds, which played an active role as antibacterial agents, as comfirmed by TLC test. Antibacterial activity against both pathogens was positive, as evidenced by the formation of a clear zone in the test medium. This study provides new insights into the potential bioactivity of Cassidula nucleus as natural ingredients for medical and health applications.